Role of Birds in Dispersal of Etiologic Agents of Tick-borne Zoonoses, Spain, 2009 - Palomar, Ana M. (Centers for Disease Control and Prevention, 2012)
We amplified gene sequences from Anaplasma phagocytophilum, Borrelia garinii, B. valaisiana, B. turdi, Rickettsia monacensis, R. helvetica, R. sibirica sibirica, and Rickettsia spp. (including Candidatus Rickettsia vini) in ticks removed from birds in Spain. The findings support the role of passerine birds as possible dispersers of these tick-borne pathogens.